Effects of Dietary Management in Overweight and Obese Women with Polycystic Ovary Syndrome: A Systematic Review - Rahmawati, Nur Aini Lutfi; Padoli, Padoli; Amalindah, Dia; Hidayatin, Nur; Suryandari, CH.R. Yeni (International Journal of Psychosocial Rehabilitation, 2020)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy af ecting women of reproductive age. A comorbidity of PCOS is obesity. It is associated with excess weight gain, which, in turn, exacerbates the health burden of PCOS. Obesity, particularly visceral adiposity which is common in obese and non- obese women with PCOS, amplifies and worsens all metabolic and reproductive outcomes in PCOS. This review systematically searched databases: PubMed, SAGE, Scopus, ScienceDirect, Ebscohost, limited to the last 5 years, 2015 until 2020. The primary outcome was weight management defined as either weight loss, weight maintenance or prevention of weight gain, dietary interventions, carbohydrate diets, diet patterns of PCOS patients. The secondary outcome of interest was ovulation. A total of 306 publications was found, with fifteen relevant studies consisting of ten randomized controlled trials, three pilot studies and two case control studies. This was 12 weeks which all dietary interventions are aimed at simple weight loss, especially through short-term reductions in dietary intake. Weight management through lifestyle intervention was crucial for PCOS management to improve fertility, pregnancy complications, risk factors for diabetes and cardiovascular disease, and psychological health. Development of these strategies for PCOS should be informed by research in reproductive-aged women and during pregnancy.